(untitled) (NEW: Emerging scholars in Australian Indigenous Studies, 2018)
This essay argues that Australia, while having made some substantive progress in the social and political reclamation of Indigenous rights, still maintains a powerful sense of colonisation. Examples surrounding the ideas of nationalism, land rights and recognition are drawn on to establish that Australia is undergoing the process of decolonisation, rather than having already done so.